MELACAK MAKNA KONSEP KERUPAAN PADA LAMBANG INSTANSI DI INDONESIA DENGAN SUMBER BENTUK MATAHARI - adisukma, wisnu (Institut Seni Indoensia Surakarta, 2019)
The article tittled Melacak Makna Konsep Kerupaan Pada Lambang Instansi di Indonesia dengan Sumber Bentuk Matahari is intended to pursue the textual and contextual meaning of institution sign with basic shape of sun. With iconographic approach would be obtained deeper and broader meaning from a work of art. Through this approach, the artwork will be a major concern in reviewing the history of art, nevertheless still necessary to understand the contextual and symbolic aspects. As the results, sign with basic shape of sun is the cosmic center, cental, foundation point, origin, sangkan paran, or axis mundi. Therefore, it is as the sun that is the problem solving of many problematics in its era.